PEMBERDAYAAN USAHA KESEHATAN SEKOLAH MELALUI PELATIHAN DOKTER KECIL DI SDN 31 PASIA NAN TIGO KECAMATAN KOTO TANGAH KOTA Padang - Syafrawati syafrawati; Vivi Triana; M. Ikhsan Novind; Prima Kurniati Hamzah (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
UKS is part of the school-age child health program. Problems that often arise in the implementation of UKS are that the use of UKS space is not optimal and a cadre of students has not been formed in a sustainable manner to become UKS administrators, and the role of UKS at the elementary school level is not optimal in order to improve the health status of school-age children. Based on secondary data, it was found that the implementation of School Health Business at SDN 31 Pasia Nan Tigo, Koto Tangah District was not optimal. In addition, diseases caused by behavioral factors such as diarrhea, ARI, and helminthiasis, are still health problem that still often appears among the school-age group in this area, therefore it is necessary to develop and develop UKS activities by holding Little Doctor Training. The purpose of this activity is to form a small doctor so that the implementation of UKS is better so that school-age children can improve their own health and the health of others around them, especially their peers. or simulation. This activity went well. The participants participated in the activity enthusiastically and were able to answer the questions given at the end of the session. This activity can also increase the knowledge of small doctors about first aid. It is suggested to the school be able to cooperate with the Puskesmas in the Pasia Nan Tigo area to conduct comprehensive training of minor doctors.